Determinants of RoE of S&P BSE Sensex Companies : A Panel Data Analysis - Sriram, M. (Indian Journal of Finance, 2018)
The present study analyzed the determinants of RoE (return on equity) for a sample of 22 companies drawn from S&P BSE Sensex in India for a period of 6 years. The study found that on an average, companies gave a RoE of 19.7% and RoA (return on assets) of 16.4% to the shareholders and investors in total during the period of study. The average equity multiplier (EM) was 1.434 which shows that companies had used significant amount of debt to finance the purchase of assets. The study demonstrated that a fixed effect panel data analysis is much better than the pooled OLS regression results to explain variation in RoE. RoE is not only influenced significantly by RoA, but also by company specific characteristics which the conventional model fails to capture. Hausman test was run to decide on whether a fixed effect model or random effect model will be suited for the analysis. Wald c2 test suggested that a panel data model is a better explanatory model than pooled OLS model. The study also provides directions for future research.